Automatic Adjustment of the Inspiratory Trigger and Cycling-Off Criteria Improved Patient-Ventilator Asynchrony During Pressure Support Ventilation - Ling Liu (Frontiers Media S.A., 2021)
Background: Patient-ventilator asynchrony is common during pressure support ventilation (PSV) because of the constant cycling-off criteria and variation of respiratory system mechanical properties in individual patients. Automatic adjustment of inspiratory triggers and cycling-off criteria based on waveforms might be a useful tool to improve patient-ventilator asynchrony during PSV.Method: Twenty-four patients were enrolled and were ventilated using PSV with different cycling-off criteria of 10% (PS10), 30% (PS30), 50% (PS50), and automatic adjustment PSV (PSAUTO). Patient-ventilator interactions were measured.Results: The total asynchrony index (AI) and NeuroSync index were consistently lower in PSAUTO when compared with PS10, PS30, and PS50, (P < 0.05). The benefit of PSAUTO in reducing the total AI was mainly because of the reduction of the micro-AI but not the macro-AI. PSAUTO significantly improved the relative cycling-off error when compared with prefixed controlled PSV (P < 0.05). PSAUTO significantly reduced the trigger error and inspiratory effort for the trigger when compared with a prefixed trigger. However, total inspiratory effort, breathing patterns, and respiratory drive were not different among modes.Conclusions: When compared with fixed cycling-off criteria, an automatic adjustment system improved patient-ventilator asynchrony without changes in breathing patterns during PSV. The automatic adjustment system could be a useful tool to titrate more personalized mechanical ventilation.